How resistant is 'treatment‐resistant' obsessive‐compulsive disorder in youth?. (31st July 2014) - Krebs, Georgina; Isomura, Kayoko; Lang, Katie; Jassi, Amita; Heyman, Isobel; Diamond, Holly; Advani, Jana; Turner, Cynthia; Mataix‐Cols, David
<x xml:space="preserve">Abstract</x> Objectives Obsessive‐compulsive disorder (OCD) is often perceived as being difficult to treat. This study aimed to test the hypothesis that treatment non‐response in routine clinical practice is often due to failures in the delivery of treatment, and that most patients who are apparently treatment‐resistant will respond to treatment if adequately delivered. Design Retrospective cohort data analysis. Methods Forty‐three young people with severe, treatment‐resistant OCD (defined as Children's Yale‐Brown Obsessive‐Compulsive Scale [CY‐BOCS] scores ≥30 and non‐response to previous cognitive behaviour therapy [CBT] and selective serotonin reuptake inhibitors) were referred to a specialist clinic and completed a course of manualized CBT, with (N = 21) or without (N = 22) optimization of medication. A sub‐sample (N = 15) completed a semi‐structured interview to determine characteristics of their previous CBT; quality was assessed according to pre‐determined criteria. Results Specialist treatment was associated with significant reductions in OCD symptoms at post‐treatment with gains maintained at 3‐month follow‐up. At the 3‐month follow‐up, 58% of patients showed a meaningful clinical response (≥35% drop on the CY‐BOCS) and 22% were in remission (≤12 on the CY‐BOCS). Patients whose medication was optimized tended (non‐significantly) to have better responses. The quality of previous CBT was assessed in a sub‐group of participants and rated as inadequate in 95.5% of cases. The most common inadequacy was insufficient focus on exposure techniques. Conclusions These findings provide support for the notion that treatment non‐response in routine practice may be due to technical treatment failures and highlight the need to disseminate good quality evidence‐based treatment among this population. Research is also needed to understand factors that impede outcome to further improve response and remission rates. Practitioner points Among young people with OCD, failure to respond to treatment in routine clinical practice may often reflect the nature of the treatment received. Exposure techniques may often be overlooked in CBT for OCD, potentially resulting in poor therapeutic response. Most young people with severe and apparent treatment‐resistant OCD respond to outpatient CBT incorporating E/RP. Further research is needed to establish effective methods for disseminating good quality CBT for OCD.